2020
DOI: 10.1177/0253717620957563
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden and Disability in Somatoform Disorder: An Exploratory Study

Abstract: Background: Very few Indian studies have explored disability among patients with somatoform disorder and the burden experienced by their caregivers. We aimed to assess the levels of disability among patients with somatoform disorder and the levels of burden among their caregivers and compare these parameters against patients with schizophrenia. Methods: Participants included adults with a diagnosis of somatoform disorders (F45.0–F 45.9) ( n = 28) or schizophrenia (F20.0–F20.9) ( n = 28) diagnosed as per the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Burden and Disability in Somatoform Disorder: An Exploratory Study" W e thank Andrade et al for their interest and critical appraisal of our published article. 1 They have raised an important issue: the unexpected finding of comparable disability between somatoform disorder and schizophrenia. We agree with the explanations provided by the authors, which we also had pointed out; the study setting would have naturally biased the sample toward a more severely ill sample of patients with somatoform disorder, as is the case with all facility-based studies.…”
Section: Responses To the Comments On "Caregivermentioning
confidence: 99%
“…Burden and Disability in Somatoform Disorder: An Exploratory Study" W e thank Andrade et al for their interest and critical appraisal of our published article. 1 They have raised an important issue: the unexpected finding of comparable disability between somatoform disorder and schizophrenia. We agree with the explanations provided by the authors, which we also had pointed out; the study setting would have naturally biased the sample toward a more severely ill sample of patients with somatoform disorder, as is the case with all facility-based studies.…”
Section: Responses To the Comments On "Caregivermentioning
confidence: 99%
“…It has been reported that the severity of somatic symptoms was positively associated with the direct and indirect costs for patients with SFD [ 10 ]. An Indian study showed that patients with SFD experience considerable levels of disability, and that their caregivers go through various levels of burden in daily life; this burden is comparable to the one for schizophrenia [ 11 ]. Thus, early screening for patients at high risk for SFD is imperative to improve the diagnosis of SFD and to reduce the associated economic burden.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the physical symptoms, patients with SFD often suffer from depressive symptoms. Van den Bergh and colleagues [ 11 ] suggested that persons with (MUS) SSD and persons with depression disorder share the trait of dispositional negativity as a general vulnerability for psychopathology. Therefore, this study also used two classic scales, PHQ-15 and PHQ-9, to evaluate the physical symptoms and depressive emotions of the subjects, in order to comprehensively reflect their clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…
BackgroundSomatoform disorder is a disorder characterized by the presence of multiple symptoms that cannot be explained or proven as physical symptoms. Patients with this disorder often undergo examinations and consultations with various healthcare centres about their complaints [1]. Doctors on duty in the emergency department often misdiagnose this disorder with other diagnoses.
…”
mentioning
confidence: 99%